High-voltage kV-class AlN metal-semiconductor field-effect transistors on single-crystal AlN substrates - Bingcheng Da; Dinusha Herath Mudiyanselage; Dawei Wang; Ziyi He; Houqiang Fu (Applied Physics Express)
This letter reports the demonstration and electrical characterization of high-voltage AlN metal-semiconductor field-effect transistors (MESFETs) on single-crystal AlN substrates. Compared with AlN MESFETs on foreign substrates, the AlN-on-AlN MESFETs showed high breakdown voltages of over 2 kV for drain-to-gate spacing of 15 μm and one of the highest average breakdown fields among reported AlN MESFETs. Additionally, the devices also exhibited decent drain saturation current and on/off ratio without complicated regrown or graded contact layers, which are several times higher than those of reported AlN-on-sapphire MESEFTs. This work is beneficial for the future development of ultrawide bandgap AlN power electronics.